Retinoblastoma-repression of E2F-dependent transcription depends on the ability of the retinoblastoma protein to interact with E2F and is abrogated by the adenovirus E1A oncoprotein. - Arroyo, M (1992)
The product of the retinoblastoma tumor suppressor gene interacts with the transcription factor E2F. Two distinct types of interactions can be detected between the retinoblastoma gene product (Rb) and E2F. The first type involves an Rb-binding protein, RBP60. The Rb/E2F complex formed in the presence of RBP60 is able to bind DNA and migrates with a distinct mobility in gel retardation assays. The second type of Rb/E2F complex is seen in the absence of RBP60. This second type of Rb/E2F complex does not form a band-shift complex in gel retardation assays and its formation results in an apparent inhibition or loss of the DNA binding activity of E2F. Using a series of Rb-mutants we show that these two types of Rb/E2F complexes depend on common domains of the Rb protein. The T/E1A-binding region as well as the carboxyl-terminus of the Rb protein are critical for these two types of Rb/E2F interactions. We also show that the retinoblastoma protein represses the E2F-dependent transcription, and this Rb-repression of the E2F-dependent transcription depends on the ability of Rb to interact with E2F. Moreover, the adenovirus E1A gene product, which binds Rb, counteracts the Rb-repression and restores E2F-dependent transcription.